2011
DOI: 10.1002/mus.21917
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue leads to gait changes in spinal muscular atrophy

Abstract: Gait analysis detects fatigue, and the decrement in stride length may reflect selective muscle involvement in SMA. Further understanding of the mechanisms underlying fatigue may suggest additional targets for future therapeutic interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 16 publications
4
36
0
Order By: Relevance
“…Quantitative measures of fatigue help link these subjective findings with the disease and provide insight into the pathophysiology of SMA. Stride length and gait velocity during the 6MWT have been shown to describe fatigue in ambulant SMA . In this study, gait velocity decreased by 0.19 meters/s or 21% on average from first to last minute of the 6MWT, which is consistent with our previous study .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Quantitative measures of fatigue help link these subjective findings with the disease and provide insight into the pathophysiology of SMA. Stride length and gait velocity during the 6MWT have been shown to describe fatigue in ambulant SMA . In this study, gait velocity decreased by 0.19 meters/s or 21% on average from first to last minute of the 6MWT, which is consistent with our previous study .…”
Section: Discussionsupporting
confidence: 93%
“…The Six‐Minute Walk Test (6MWT) is an assessment of walking ability that detects physiological fatigue in ambulatory SMA patients as demonstrated by a 17% decrease in gait velocity from the first minute to the last . Decrement in velocity is due to change in stride length rather than cadence, as seen in quantitative gait analysis during the 6MWT in SMA patients . Muscles that regulate stride length (hip flexor, knee extensor, and gastrocnemius muscles) demonstrate weakness in SMA.…”
mentioning
confidence: 99%
“…113 Fatigue Physiologic fatigue is a common complaint in patients with milder SMA and can be measured by the decrement in distance walked from the first to sixth minute of the six-minute walk test. [114][115][116] The mechanism(s) underlying fatigue in SMA remains to be elucidated but may be related at least in part to the neuromuscular junction defects (described previously). Anecdotal evidence suggests that oral albuterol in usual pediatric doses is an effective agent in the treatment of fatigue in SMA patients, thus is frequently used; however, fatigue has not been studied directly in the conducted albuterol pilot studies that showed improvement in motor function.…”
Section: Orthopedicmentioning
confidence: 95%
“…This recognition and the ability to intervene using noninvasive ventilation protocols have resulted in a dramatic increase in life expectancy among severely affected SMA patients. Patients born between 1995 and 2006 were reported to exhibit a 70% reduced risk of death compared with those born between 1980 and 1994, over a mean follow-up of approximately 50 months [79]. Of equal concern in many SMA patients are complications that are orthopedic in nature.…”
Section: Treatment Of Smamentioning
confidence: 99%